InGaN/GaN multiple-quantum-well light-emitting diodes with a grading InN composition suppressing the Auger recombination - Zhang, Zi-Hui (2015)
In conventional InGaN/GaN light-emitting diodes (LEDs), thin InGaN quantum wells are usually adopted to mitigate the quantum confined Stark effect (QCSE), caused due to strong polarization induced electric field, through spatially confining electrons and holes in small recombination volumes. However, this inevitably increases the carrier density in quantum wells, which in turn aggravates the Auger recombination, since the Auger recombination scales with the third power of the carrier density. As a result, the efficiency droop of the Auger recombination severely limits the LED performance. Here, we proposed and showed wide InGaN quantum wells with the InN composition linearly grading along the growth orientation in LED structures suppressing the Auger recombination and the QCSE simultaneously. Theoretically, the physical mechanisms behind the Auger recombination suppression are also revealed. The proposed LED structure has experimentally demonstrated significant improvement in optical output power and efficiency droop, proving to be an effective solution to this important problem of Auger recombination.